2009
DOI: 10.5191/jiaee.2009.16105
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Doctoral-Level Content in International Agricultural and Extension Education–2010: Viewpoint of Fifteen Engaged International Scholars

Abstract: Given an increasingly interconnected world with an expanding knowledge base, this research engaged 15 international scholars to resolve two research questions: (a) what are the knowledge objects that are essential for the doctoral-level professional working in international agricultural and extension education in 2010, and (b) what are the knowledge domains that coalesce and organize knowledge objects by general principles? Using the Delphi method, scholars engaged in three rounds to identify, rate, and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 20 publications
(11 reference statements)
3
34
0
Order By: Relevance
“…We defined consensus a priori as items that achieved two-thirds consensus of agree or strongly agree (Boyd, 2003;Conner, Roberts, & Harder, 2013;Shinn, Wingenbach, Briers, Lindner, & Baker, 2009). Individual items that achieved consensus in round two advanced to round three and were subject to an iteration of the same process and criteria.…”
Section: Round Twomentioning
confidence: 99%
“…We defined consensus a priori as items that achieved two-thirds consensus of agree or strongly agree (Boyd, 2003;Conner, Roberts, & Harder, 2013;Shinn, Wingenbach, Briers, Lindner, & Baker, 2009). Individual items that achieved consensus in round two advanced to round three and were subject to an iteration of the same process and criteria.…”
Section: Round Twomentioning
confidence: 99%
“…Competencies for evaluators include a broad taxonomy including professional practice, systematic inquiry, social science research methods, situational analysis, project management, and reflective practice (Conner et al, 2013;Kock & Weeks, 2015;Shinn et al, 2009;Stevahn et al, 2005). Ghimire and Martin (2011) reported that extension staff require skills in assessing learning experiences and outcomes, evaluating program results, assessing program impacts, and using impact data for planning future programs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Donors require accountability for expenditures through a process of monitoring and evaluation (M&E). NGO and extension staff should possess program planning, needs assessment, and evaluation skills to be effective in their roles (Shinn, Wingenbach, Briers, Lindner, & Baker, 2009;Strong & Harder, 2011). Gaining M&E skills is a process of formal education, on-the-job training, and support from employers through evaluation capacity building continuing education (Ghimire & Martin, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar or duplicated statements (i.e. skills) were combined or eliminated while compound statements were separated (Shinn, Wingenbach, Briers, Lindner, & Baker, 2009). These skills were analyzed by a panel of experts, grouped into 23 skill areas, and were used to develop the round 2 questionnaire (see Table 1).…”
Section: Round Onementioning
confidence: 99%